We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
153
1
avatar

3.8x-(-1-9.7x)=2.6+13.3x

Please help I don't have a clue!!

 Oct 11, 2018

Best Answer 

 #1
avatar+101761 
+2

\(3.8x-(-1-9.7x)=2.6+13.3x\\ 3.8x{\color{red}+}-{\color{red}1} (-1-9.7x)=2.6+13.3x\\ 3.8x\qquad +1+9.7x\quad =2.6+13.3x\\ 3.8x\qquad +9.7x +1\quad =2.6+13.3x\\ \qquad 13.5x \qquad+1\quad =2.6+13.3x\\ \text{now subtract 13.3x from both sides}\\ \qquad 0.2x \qquad+1\quad =2.6\\ \text{ Now subtract 1 from both sides }\\ \qquad 0.2x \qquad \qquad =1.6\\ \text{ Now divide both sides by 0.2 }\\ \qquad x \qquad \qquad =1.6\div 0.2\\ \qquad x \qquad \qquad =8\\ \)

.
 Oct 11, 2018
 #1
avatar+101761 
+2
Best Answer

\(3.8x-(-1-9.7x)=2.6+13.3x\\ 3.8x{\color{red}+}-{\color{red}1} (-1-9.7x)=2.6+13.3x\\ 3.8x\qquad +1+9.7x\quad =2.6+13.3x\\ 3.8x\qquad +9.7x +1\quad =2.6+13.3x\\ \qquad 13.5x \qquad+1\quad =2.6+13.3x\\ \text{now subtract 13.3x from both sides}\\ \qquad 0.2x \qquad+1\quad =2.6\\ \text{ Now subtract 1 from both sides }\\ \qquad 0.2x \qquad \qquad =1.6\\ \text{ Now divide both sides by 0.2 }\\ \qquad x \qquad \qquad =1.6\div 0.2\\ \qquad x \qquad \qquad =8\\ \)

Melody Oct 11, 2018

11 Online Users

avatar
avatar
avatar